Luminescence based on energy transfer in xerogels doped with Tb2–xEux(WO4)3 - Grobelna, Beata (Oficyna Wydawnicza Politechniki Wrocławskiej, 2008)
A series of luminescent materials consisting of Tb2–xEux (WO4)3 entrapped in silica xerogel were successfully prepared. The parameter x in the formula changed from 0.4 to 2. Spectroscopic properties such as absorption and luminescence of optically active ions were studied at room temperature. Owing to the energy transfer from the WO42- groups (ligand–metal charge transfer, (LMCT)) the lanthanide ions show their characteristic emissions in Tb2–xEux(WO4)3 entrapped in silica xerogel, i.e., 5D0 → 7FJ (J = 0, 1, 2, 3, 4) transition for Eu3+ ion and 5D4 → 7FJ (J = 6, 5, 4, 3) transition for Tb3+ ion. The energy transfer is effective for the mixed tungstate salt Tb1.35Eu0.65(WO4)3 entrapped in silica xerogel. The Eu(III) emission intensity in the materials under study increases with an increase in the annealing temperature from 600 to 900 °C. This is due to the removal of the effective O –H quenchers from the coordination sphere of the Eu(III) ion.
Optica Applicata, Vol. 38, 2008, nr 1, s. 39-47
Keywords: sol-gel method; optyka; photoluminescence; lanthanide(III) ions; energy transfer